Descending Stairs in Patients after Total Knee Arthroplasty Fails to Reproduce Efferent Knee Joint Extension Moment in Healthy Volunteers - FURUMOTO, Taiki; KAWAMURA, Yuka; KATOH, Shinsuke; HAMADA, Daisuke; SAIRYO, Koichi; KATAYAMA, Ayane; TOMONARI, Ken; MATSUI, Yu (Physical Therapy Japan, 2020)
Purpose: To clarify whether a patient can reproduce the elongation moment of the efferent knee joint in patient of the same age while descending stairs after total knee arthroplasty (TKA).Methods: The subjects were 8 patients in the TKA group who were able to perform step-down movements in one step and 1 step 1 year after undergoing TKA, and 10 healthy volunteers of the same age. In the descending motion analysis, lower limb muscle activity was measured using a three-dimensional motion analyzer and ground reaction force meter by measuring the joint angle, joint moment, joint power, and surface electromyogram of the sagittal plane. All measured data were compared for the main measurement item, first peak of knee extension moment (20%), and second peak of knee extension moment (80%).Results: In the TKA group, the elongating moment of the efferent knee joint during the lowering movement was significantly lower in both the early stance phase and late stance phase than that in the healthy group.Conclusion: One year after the TKA, the efferent knee joint extension moment of healthy individuals of the same age cannot be reproduced while descending stairs.